Enhancing Customer Experience in Car Servicing: Insights from Indian Markets - Mannadhan, Prabhu; G, Madan Mohan (International Journal of Engineering and Management Sciences, 2024)
This descriptive research has attempted to assess customers’ satisfaction with services offered by car servicing firms in India. The researcher administered a structured questionnaire to 300 company customers, selected using the Systematic Random Sampling technique. Data collected were analyzed using SPSS, applying the analytical tools of Frequency, Percentage, Mean, factor analysis, cluster analysis, Chi-square and Correspondence Analysis. Results of the study have revealed that the caring nature of servicing staff, the quality of services and service personnel, and the convenience and comfort offered to customers have been identified as the most important factors affecting customer satisfaction.